2001
DOI: 10.1300/j013v34n02_06
|View full text |Cite
|
Sign up to set email alerts
|

“Staying Strong”: How Low-Income Rural African American Women Manage Their Menopausal Changes

Abstract: The present study sought to describe the various ways a group of rural, low-income African American women interpreted and responded to menopausal changes. The study analyzed the experiences of 44 African American women over the age of 40 from a small rural town in a large Eastern state; all interviews took place in the women's homes. Inductive analysis of the interviews uncovered two key concepts women employed in the face of menopausal changes: turning inward and relying on one's own resources and turning out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, each woman's socioeconomic background informed their unique experience of their body-selves. Whereas one unemployed single woman struggling with housing and work had no time for indulging in menopause, akin to Nixon et al's (2001) rural African American women "staying strong," another woman in similar circumstance found the image of fertility loss was "killing her" inside with the consequent need to "move on. "…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, each woman's socioeconomic background informed their unique experience of their body-selves. Whereas one unemployed single woman struggling with housing and work had no time for indulging in menopause, akin to Nixon et al's (2001) rural African American women "staying strong," another woman in similar circumstance found the image of fertility loss was "killing her" inside with the consequent need to "move on. "…”
Section: Discussionmentioning
confidence: 99%
“…Meaning arises from the interaction between the biological and social where lived bodily experiences become social or visible to oneself and others (1993,2010). Somatic experiences of menopause may vary cross-culturally (Beyene, 1986;Lock & Kaufert, 2001;Shea, 2006), socioeconomically (Dasgupta & Ray, 2013;Delanoe et al, 2012), ethnically (Nixon, Mansfield, Kittell, & Faulkner, 2001;Sampselle, Harris, Harlow, & Sowers, 2002;Wray, 2007), and across generations (Davis, 1997;Utz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There has been some effort to examine cultural differences in North American menopause research over the past few years (e.g. Adler et al, 2000;Nixon, Kernoff-Mansfield, Kittell, & Faulkner, 2001), supporting the notion that beliefs about menopause are affected by cultural variables.…”
Section: Limitationsmentioning
confidence: 99%
“…For AAW other risk factors during MT include nutritional habits, physical inactivity, and increased BMI, all of which influence depression levels (Avis et al, 2001;Bromberger et al, 2009;Nelson et al, 2008). Additionally, differences in cultural attitudes and beliefs about transition to menopause affect AAW's perceptions and management of their menopausal experience (Im et al, 2009;Nixon, 1998;Nixon, Mansfield, Kittell & Faulkner, 2001;Sampselle, Harris, Harlow & Sowers, 2002;Strickland, 2000).…”
Section: Biological Factors: Menopausal Statusmentioning
confidence: 99%
“…A subsequent study by Nixon et al (2001), among 44 rural AAW, indicated that demanding familial responsibilities forced many women to ignore their menopausal symptoms and internalize their health-related needs by "staying strong" (p.87) during MT. In contrast, findings from the study by Sampselle et al (2002), among 30 AA and EAW, which explored midlife development and perception of menopause, concluded that AAW welcomed menopause and considered it liberation from the fears of pregnancy and monthly menstrual cycles.…”
Section: Perceptions Of Menopausal Transitionmentioning
confidence: 99%